Pandemi Dan Perilaku Konsumen Dan Adaptasi Ekonomi Masyarakat - Amalia, Rani; Salsabila, Nurhacici (EL-EMIR Institute, 2024)
The COVID-19 pandemic has significantly changed consumer behavior and driven economic adaptation across the world. This study aims to investigate the impact of the pandemic on consumer behavior and the economic adaptation strategies adopted by society. The research method used is a qualitative approach through in-depth interviews with selected respondents representing various segments of society. The study results show that the COVID-19 pandemic has resulted in dramatic changes in people's shopping preferences and consumption patterns. Most respondents reported an increase in online purchases and use of digital platforms for shopping. The pandemic has also driven changes in spending behavior with a greater focus on essentials and health products. Apart from that, people also adapt economic strategies such as product diversification, business capital adjustments, and innovation in business models to survive in uncertain economic conditions. These findings highlight the importance of flexibility and innovation in dealing with the global economic crisis, and support the need for policies and strategies that strengthen society's economic resilience. The implication of this research is the need for further support for business actors and consumers to build a more adaptive and sustainable economic system in the future.